Graduate-level Instructor’s Perception of Teaching Critical Thinking - Jay Van Der Werff (Adult Education Research Conference, 2017)
Higher learning institutions identify the teaching of critical thinking skills to students as a goal of the academic programs offered. This study examined faculty perceptions for teaching critical thinking skills.
Keywords: Critical thinking; faculty development